What you see is what you get: webcam placement influences perception and social coordination - Thomas, Laura E.; Pemstein, Daniel (Frontiers in Psychology, 2015)
Building on a well-established link between elevation and social power, we demonstrate that—when perceptual information is limited—subtle visual cues can shape people’s representations of others and, in turn, alter strategic social behavior. A cue to elevation (unrelated to physical size) provided by the placement of web cameras in a video chat biased individuals’ perceptions of a partner’s height (Exp. 1) and shaped the extent to which they made decisions in their own self-interest: participants tended to coordinate their behavior in a manner that benefitted the preferences of a partner pictured from a low camera angle during a game of asymmetric coordination (Exp. 2). Our results suggest that people are vulnerable to the influence of a limited viewpoint when forming representations of others in a manner that shapes their strategic choices.